Diagnosing Water Problem for Asmari Reservoir in Abu Ghirab Oilfield Using Analytical and Numerical Approaches (Journal of Engineering, 2020)
Asmari is the main productive reservoir in Abu Ghirab oilfield in the south-east part of Iraq. It has history production extends from 1976 up to now with several close periods. Recently, the reservoir suffers some problems in production, which are abstracted as water production rising with oil production declining in most wells. The water problem type of the field and wells is identified by using Chan's diagnostic plots (water oil ratio (WOR) and derivative water oil ratio (WOR') against time). The analytical results show that water problem is caused by the channeling due to high permeability zones, high water saturation zones, and faults or fracturing. The numerical approach is also used to study the water movement inside the reservoir. A three dimensional geological and a three phase reservoir model was constructed for Asmari reservoir. The simulation model was used to visualize the water front advance in order to evaluate the water production structurally. The numerical results also show that the channeling is the main cause of water production, as well as, oil-water contact advance problem was noted due to fault sealing behavior effects.